The effects of dietary nitrate supplementation on endurance exercise performance and cardiorespiratory measures in healthy adults: a systematic review and meta-analysis. Issue 1 (9th July 2021) - Gao, Chloe; Gupta, Saurabh; Adli, Taranah; Hou, Winston; Coolsaet, Reid; Hayes, Abigail; Kim, Kevin; Pandey, Arjun; Gordon, Jacob; Chahil, Gurneet; Belley-Cote, Emilie P.; Whitlock, Richard P.
Abstract: Background: Nitrate supplementation is thought to improve performance in endurance sports. Objective: To meta-analyze studies evaluating the effect of nitrate supplementation on endurance sports performance among adults. Data sources: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, EMBASE, Web of Science and CINAHL without language restrictions. Methods: We included studies that: 1) compared nitrate supplementation with placebo; 2) enrolled adults engaging in an endurance-based activity; and 3) reported a performance measure or surrogate physiologic outcome. We evaluated risk of bias using the Cochrane Collaboration tool and pooled data with a random-effects model. We used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to evaluate confidence in estimates. Results: We included 73 studies ( n  = 1061). Nitrate supplementation improved power output (MD 4.6 watts, P  < 0.0001), time to exhaustion (MD 25.3 s, P  < 0.00001), and distance travelled (MD 163.7 m, P  = 0.03). We found no significant difference on perceived exertion, time trial performance and work done. Nitrate supplementation decreased VO2 (MD − 0.04 L/min, P  < 0.00001) but had no significant effect on VO2max or blood lactate levels. Conclusion: The available evidence suggests that dietary nitrate supplementation benefits performance-related outcomes for endurance sports.